2017
DOI: 10.1002/pola.28570
|View full text |Cite
|
Sign up to set email alerts
|

Functional polyisobutylenes via electrophilic cleavage/alkylation

Abstract: Lewis-acid catalyzed degradation of poly(isobutylene-co-isoprene) (butyl rubber) in the presence of an alkoxybenzene compound was studied as a new route toward low molecular weight multifunctional polyisobutylenes. Simultaneous cleavage and functionalization of butyl rubber was conducted at 270 8C and 240 8C under TiCl 4 or AlCl 3 catalysis in 60/40 hexane/methylene chloride cosolvents in the presence of (3-bromopropoxy)benzene (BPB) for various times up to 24 h. The butyl rubber (EXXON TM Butyl 365) possessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…A wide range of EW Q s and average functionalities (F n ) can be obtained by varying temperature, reaction time, F IP of the butyl rubber starting material, identity/concentration of the Lewis acid, quencher (i.e., Friedel–Crafts substrate) concentration, and butyl rubber concentration. Recently, our laboratory reported the cleavage/alkylation reaction of butyl rubber (F IP = 0.0230) using (3‐bromopropoxy)benzene . The latter is a versatile quencher that yields primary‐bromide functional groups along the PIB backbone for easy synthetic modification .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A wide range of EW Q s and average functionalities (F n ) can be obtained by varying temperature, reaction time, F IP of the butyl rubber starting material, identity/concentration of the Lewis acid, quencher (i.e., Friedel–Crafts substrate) concentration, and butyl rubber concentration. Recently, our laboratory reported the cleavage/alkylation reaction of butyl rubber (F IP = 0.0230) using (3‐bromopropoxy)benzene . The latter is a versatile quencher that yields primary‐bromide functional groups along the PIB backbone for easy synthetic modification .…”
Section: Resultsmentioning
confidence: 99%
“…Characterization via GPC/MALLS indicated that Butyl 068 had a number average molecular weight (normalMfalse¯n) of 3.37 × 10 5 g/mol and a dispersity (Ð) of 1.29. 1 H NMR analysis showed that the mole fraction of isoprene (IP) comonomer units in the copolymer, F IP , was equal to 0.0108, and that the average IB homopolymer sequence length, n IB = IB units/IP units (assuming isolated IP units) was 91.6 . From the latter value, the isoprene equivalent weight, EW IP , was calculated to be 5.21 × 10 3 g/mol .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations